THE VERBAL AND VISUAL ELEMENTS OF BEAUTY PRODUCT ADVERTISEMENTS IN INDONESIAN WOMEN’S MAGAZINES - Yuni Khairani; Busmin Gurning; Zanuddin Zainuddin (Universitas Negeri Medan, 2019)
As the development of technology, advertisers who use print media utilize image and text to achieve its economic goals. In trying to understand meaning within the advertisement, we should be able to read and interpret all the semiotic resources. This study was aimed at investigating the verbal and visual elements found in beauty product advertisements in Indonesian women’s magazine. The data were the multimodal clauses of 12 beauty products advertisements taken from three Indonesian women’s magazines, namely Femina, Cosmopolitan Indonesia and her world Indonesia which were published in March 2018 by using snowball sampling technique. In order to identify the verbal and visual elements, Cheong (2004) framework of generic structure advertisement was used. The findings showed that Display which serves to describe the product in a real and explicit way and Enhancer as the linguistic element which function is to give detail explanation about the product appear to be the obligatory elements in beauty product print advertisement. Meanwhile, elements like Lead, Announcement, Emblem, Tag, Call and Visit Information are optional in the structure of print advertisements. Thus, it is found a new GSP of beauty product advertisement as following: (Lead)^ Display^ (Announcement)^Enhancer^(Emblem)^(Tag)^(Call and Visit Information).Keywords: Verbal and Visual, Beauty Advertisements, Indonesian Women’s Magazine